2020
DOI: 10.1093/brain/awaa246
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage-associated inflammation highlights biomarkers in PRKN/PINK1 parkinsonism

Abstract: There is increasing evidence for a role of inflammation in Parkinson’s disease. Recent research in murine models suggests that parkin and PINK1 deficiency leads to impaired mitophagy, which causes the release of mitochondrial DNA (mtDNA), thereby triggering inflammation. Specifically, the CGAS (cyclic GMP-AMP synthase)-STING (stimulator of interferon genes) pathway mitigates activation of the innate immune system, quantifiable as increased interleukin-6 (IL6) levels. However, the role of IL6 and circulating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 38 publications
(57 reference statements)
1
102
1
Order By: Relevance
“… Blood (cell fractions)—qPCR Stratification, efficacy ( 201 , 202 , 203 ) ccf-mtDNA Reduced in PD CSF but increased in serum of PINK1 and Parkin PD patients. CSF—qPCR Stratification, efficacy (may require treatment-naive patients) ( 204 , 241 , 242 ) Inflammation IL-6 Elevated in serum of sporadic PD patients, Parkin PD patients, and Parkin heterozygotes. Some studies have found correlations between IL-6 levels and PD severity.…”
Section: Biomarkers For Developing Mitophagy-enhancing Therapies In Pmentioning
confidence: 99%
See 1 more Smart Citation
“… Blood (cell fractions)—qPCR Stratification, efficacy ( 201 , 202 , 203 ) ccf-mtDNA Reduced in PD CSF but increased in serum of PINK1 and Parkin PD patients. CSF—qPCR Stratification, efficacy (may require treatment-naive patients) ( 204 , 241 , 242 ) Inflammation IL-6 Elevated in serum of sporadic PD patients, Parkin PD patients, and Parkin heterozygotes. Some studies have found correlations between IL-6 levels and PD severity.…”
Section: Biomarkers For Developing Mitophagy-enhancing Therapies In Pmentioning
confidence: 99%
“…Some studies have found correlations between IL-6 levels and PD severity. Serum—ELISA, cytokine immunoassays Stratification, efficacy ( 156 , 204 , 206 , 207 , 208 ) Imaging Magnetic resonance spectroscopy (MRS) Hydrogen nucleus ( 1 H) MRS: N-acetylaspartate is reduced in PD patient brain and can be improved by dopamine replacement therapies. Lactate is elevated in PD patient brain.…”
Section: Biomarkers For Developing Mitophagy-enhancing Therapies In Pmentioning
confidence: 99%
“…In iPSC derived ALS patient motor neurons, TDP-43 triggered the release of mtDNA, leading to cGAS-STING activation, and neuroinflammation has been shown [ 181 ]. The induction of IL6 in response to circulating cell-free mtDNA has been reported in Parkinson patients’ serum [ 182 ]. Hence, cGAS-STING mediated inflammation emerges as another common characteristic of NDDs.…”
Section: Crosstalk Between Ddr and Other Cellular Processes Known mentioning
confidence: 99%
“…These molecules, also called mitochondrial Damage-Associated Molecular Patterns (DAMPs), which are typically released during the course of cell death, mediate inflammatory immune responses and are associated with pathogenicity and severity of various diseases. Mitochondrial DNA/DAMPs have been found in brain death, trauma patients, sepsis, neurologic (ischemic stroke and bacterial meningitis) and myocardial injury and were associated with early allograft dysfunction and acute respiratory distress syndrome (ARDS) [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. McCully et al compared the transplantation of whole mitochondria, mitochondrial components and frozen-thawed mitochondria [ 4 ].…”
Section: Safety Of Mitochondrial Transplantationmentioning
confidence: 99%